Dynamic behaviour of nuclear island structure of AP1000 under El Centro and Dien Bien earthquakes - Vu Lam, Lam Dong; Pham, Ngoc Dong; Nguyen, Dinh Kien; Nguyen, Dai Minh; Do, Tien Thinh (Nuclear Science and Technology, 2017)
AP1000 is a nuclear power plant developed by Westinghouse based on an advanced passive safety feature, and it is one of selected technologies for Ninh Thuan 2 Nuclear Power Plant. The dynamic behavior of the plant under earthquakes is the most concerned in design and construction of the plant. This paper presents a seismic analysis of the AP1000 nuclear island structure by using the computational finite element software ANSYS. A 3D finite element model for the structure is developed and its dynamic response, including the time histories for displacements, velocities and accelerations, deformed configurations and von Mises stresses of the structure are obtained for America El Centro (6.9 Richter) and Vietnam Dien Bien (5.3 Richter) earthquakes. A comparison on the dynamic response of the structure under the two earthquakes is given, and the dynamic behavior of the structure under the earthquakes is discussed.